PTH immunoassay interference: differential diagnosis with normocalcemic primary hyperparathyroidism? - Monique Nakayama Ohe; Roberto Massao Takimoto; Claudia M. Aparecida de Francischi Ferrer; Jose Viana Lima Junior; Rosa Paula Biscolla; José Gilberto Henriques Vieira; Maria Izabel Chiamolera (Archives of Endocrinology and Metabolism)
SUMMARY The main diagnostic dilemma in normocalcemic hyperparathyroidism is differentiating this condition from secondary hyperparathyroidism and other causes of elevated parathyroid hormone (PTH) levels in eucalcemic patients, including potential assay interferences. Despite the analytical sensitivity of immunoassays, they may lack adequate accuracy due to several analytical interferences, such as the presence of heterophilic antibodies. Immunoassays for PTH measurement use the immunometric "sandwich" technique, and only a few cases of interference with this assay have been reported to date. We describe herein two patients in whom PTH immunoassay interference was demonstrated. Both patients presented high serum PTH levels, measured using a second-generation Roche electrochemiluminescence assay (ECLIA; Elecsys Roche, Germany), and normocalcemia. When immunoassay interference was suspected, PTH measurements were repeated using a different analytical platform, the 1-84 PTH third-generation Roche Elecsys ECLIA, resulting in normal levels. We subsequently performed serial dilutions using normal mouse serum with the second-generation ECLIA and found no linearity, indicating the presence of interference in both patients. Immunoassay interference may lead to misinterpretation of a patient's results by the laboratory and incorrect treatment planning by the attending physician. Despite its rarity, the presence of interferences in the PTH immunoassay resulting in falsely high PTH levels should be considered when the laboratory result does not match the patient's clinical presentation, thus preventing erroneous diagnoses and unnecessary therapeutic procedures.